Is there a difference in the phthalate exposure between adults with metabolic disorders and healthy ones? - Stepanović, Kristina; Vuković, Bojan; Milanović, Maja; Milošević, Nataša; Bosić Živanović, Dragana; Stojadinović, Aleksandra; Tomić Naglić, Dragana; Lepić, Sanja; Milić, Nataša; Medić Stojanoska, Milica (Vojnosanitetski pregled, 2022)
Background/Aim. Phthalates are recognized as endocrine-disrupting compounds and are extensively present in a variety of everyday products. Chronic exposure to phthalates is suspected to be associated with a range of health disorders. The aim of the study was to examine the abundance of phthalate metabolites in the urine samples among adults in the Autonomous Province of Vojvodina, Serbia, and to determine the prevalence of phthalate metabolites in healthy individuals and those with metabolic disorders such as obesity and newly diagnosed type 2 diabetes mellitus (T2DM).Methods. For the study purpose, the first morning urine sample of 308 participants was screened for the presence of 10 phthalate metabolites: mono-ethyl phthalate (MEP), mono-(2-ethylhexyl) phthalate (MEHP), mono-n-butyl phthalate (MBP), mono-iso-allyl phthalate (MiAP), mono-n-allyl phthalate (MnAP), mono-cyclohexyl phthalate (MCHP), mono-benzyl phthalate (MBzP), mono-n-octyl phthalate (MOP), mono-n-propyl phthalate (MPP) and mono-methyl phthalate (MMP).Results. At least one phthalate metabolite was detected in the first morning urine sample in 50.32% of the examined population. The most frequently detected phthalate metabolites were MEP and MEHP. Out of all phthalate-positive participants, 38.3% of them had one, 10.7% had two, while 1.3% of participants had three phthalate metabolites in the first morning urine sample. A significant difference (p
Keywords: endocrine system diseases; phthalic acid; monoethyl phthalate; risk assessment; serbia.